Incidence rate of anemia in inflammatory bowel diseases - Atuğ, Özlen; Kani, Haluk Tarık; Banzragch, Munkhtsetseg; İmeryüz, Neşe and Akın, Hakan (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: To determine the incidence rate and distribution of anemia types over time from an Inflammatory Bowel Disease (IBD) patient cohort spanning 18 years. Materials and Methods: Between January 1995 and November 2013, the University Hospital digital databases as well as hard copies of patients’ files were reviewed retrospectively. IBD patients with at least one complete blood count (CBC) report were included in this study. Results: We obtained 941 IBD patients’ records; 375 (39.9%) patients were diagnosed with Crohn’s disease (CD), and 566 (60.1%) patients had ulcerative colitis (UC). Anemia was detected in 548 (58.2%) patients. Female patients were more frequently anemic than male patients (68.4% vs. 49.7%, p=0.001). The frequency of anemia was slightly higher in patients with CD (62.1%) than in patients with UC (55.7%) (p=0.04). The incidence rate of anemia for the entire IBD patient cohort was calculated as 103.45 per 1,000 patient-years. The correlation between the age of the IBD disease and the presence of anemia exhibited a high correlation coefficient of Pearson’s r=0.702. Conclusion: This is the first study to report the incidence rate of anemia (103.45 per 1,000 patient-years) in a long-term cohort of IBD patients.